A novel Ti/Al interpenetrating phase composite with enhanced mechanical properties - Li, Zhou; Mo, Haotian; Tian, Jiahao; Li, Jiahao; Hu, Xiao; Xia, Shiqi; Lu, Yao; Jiang, Zhengyi (Elsevier, 2024)
Lightweight, energy-absorbing materials with excellent mechanical properties are highly desired in practical engineering applications. A novel Ti-Al interpenetrating phase composite (Ti/Al IPC) was successfully fabricated by filling an Al alloy (ZL102) in the pores of an additively manufactured triply periodic minimal surface (TPMS) structure composed of Ti alloy (TC4). This IPC demonstrates a remarkable combination of attributes, including a high yield stress of 305 MPa, a Young's modulus of 64 GPa, and an ultimate tensile strength of 420 MPa. These mechanical properties are 1.5 to 2.9 times stronger than those of a single TC4 TPMS structure of the same size. The enhanced performance can be attributed to the synergistic strengthening and toughening effect resulting from the internal interpenetration of the ZL102 phase within the structure.
Keywords: Additive manufacturing; Triply periodic minimal surface; Interpenetrating phase composites; Porous structure; Fracture behaviour